Impaired Autophagy and Defective T Cell Homeostasis in Mice with T Cell-Specific Deletion of Receptor for Activated C Kinase 1 - Qiu, Guihua; Liu, Jian; Cheng, Qianqian; Wang, Qingyang; Jing, Zhaofei; Pei, Yujun; Zhao, Min; Wang, Jing; Guo, Jessie Yanxiang; Zhang, Jiyan (Frontiers in Immunology, 2017)
Autophagy plays a central role in maintaining T cell homeostasis. Our previous study has shown that hepatocyte-specific deficiency of receptor for activated C kinase 1 (RACK1) leads to lipid accumulation in the liver, accompanied by impaired autophagy, but its in vivo role in T cells remains unclear. Here, we report that mice with T cell-specific deletion of RACK1 exhibit normal intrathymic development of conventional T cells and regulatory T (Treg) cells but reduced numbers of peripheral CD4+ and CD8+ T cells. Such defects are cell-intrinsic with impaired mitochondrial clearance, increased sensitivity to cell death, and decreased proliferation that could be explained by impaired autophagy. Furthermore, RACK1 is essential for invariant natural T cell development. In vivo, T cell-specific loss of RACK1 dampens concanavalin A-induced acute liver injury. Our data suggest that RACK1 is a key regulator of T cell homeostasis.